Meninjau Ulang Undang-Undang Kehutanan Indonesia: Urgensi Revisi UU No. 41 Tahun 1999 di Era Perhutanan Sosial dan Perubahan Iklim - Ardyanto, Niko; Wulandari, Christine (MAKILA, 2025)
Law No. 41 of 1999 on Forestry constitutes the cornerstone of Indonesia’s forest governance framework. Nevertheless, as the forestry sector evolves, the law demonstrates limited adaptability to emerging issues such as social forestry and carbon trading mechanisms such as social forestry, the recognition of customary communities, carbon market mechanisms, and integrated forest-based enterprises. This study adopts a qualitative descriptive approach grounded in literature review and secondary data analysis to evaluate the substance of Law No. 41/1999 and its alignment with contemporary governance demands. The results indicate that the law remains centralized in nature, lacks explicit provisions for community-based forest management, and does not encompass legal instruments related to carbon valuation or trading schemes. Although subsequent policies such as the Job Creation Law and the Minister of Environment and Forestry Regulation No. 8/2021 have partially responded to these gaps, the overarching legal framework remains misaligned with current realities. The study concludes that a comprehensive revision is essential to reinforce legal clarity, embed ecological and social justice principles, and strengthen the forestry sector’s role in advancing national economic growth and achieving Indonesia’s global climate commitments.